Proceedings of the Integrated Crop Management Conference 1997
DOI: 10.31274/icm-180809-573
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Soil Survey Crop Yield Interpretations for Two Central Iowa Farms

Abstract: Hillel. D. 1982. [ncrodu~cion co soil physics. Acade• mic Press. :-:ew York. Jury. W.A .. and E.E. ,\tiller. 1974 , 'vfeasuremenc of che cransporc coefficients for coupled How of h"c •nd moisture 1n a rr:edium soil. Soil Sci• ence Sociery of Amer~ca Proceedings 38:55l-55i.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The field was characterized by low‐relief swell and swale topography representative of the Des Moines lobe of the Cary substage of glaciation. Detailed information on the soils can be found in Steinwand and Fenton (1995) and Steinwand et al (1996) Field management was typical for Iowa and has been described in detail in Karlen and Colvin (1992) and Colvin et al (1997) The field has been in a 2‐yr rotation of corn and soybean since 1957. For the past 16 yr, tillage has been by chisel plow and field cultivator, and a 76‐cm row spacing has been used.…”
Section: Methodsmentioning
confidence: 99%
“…The field was characterized by low‐relief swell and swale topography representative of the Des Moines lobe of the Cary substage of glaciation. Detailed information on the soils can be found in Steinwand and Fenton (1995) and Steinwand et al (1996) Field management was typical for Iowa and has been described in detail in Karlen and Colvin (1992) and Colvin et al (1997) The field has been in a 2‐yr rotation of corn and soybean since 1957. For the past 16 yr, tillage has been by chisel plow and field cultivator, and a 76‐cm row spacing has been used.…”
Section: Methodsmentioning
confidence: 99%
“…The Larson Field soils are primarily Hapludolls and Endoaquolls and are highly uniform across the fi eld, with only four SMUs representing the four soil series identifi ed during Order 1 mapping (Brevik et al, 2003a) (Table 1). Two of the SMUs, Ott osen (288) and Kossuth (388), comprise more than 89% of fi eld's area, and their component series qualify as similar inclusions (Brevik et al, 2003a), meaning there is litt le expected diff erence in agricultural management between the two soils (Steinwand et al, 1996). Therefore, approximately 90% of this fi eld is essentially uniform in terms of soil properties and anticipated response to agricultural management.…”
Section: Methodsmentioning
confidence: 99%
“…Carr et al (1991) suggested that soil series could be used to direct site‐specific management as long as soil series were identified and mapped accurately. Steinwand et al (1996) examined a 64‐ha (158 acre) field in Iowa in a Clarion–Webster–Nicollet association and found that the 1:15840 and 1:3305 scales were similar in terms of predicting crop yields within a 3‐yr study. They concluded that soil survey mapping could be used to direct site‐specific decisions.…”
mentioning
confidence: 99%